A decade of inequality in maternity care: antenatal care, professional attendance at delivery, and caesarean section in Bangladesh (1991-2004) - Ronsmans Carine; Anwar Iqbal; Collin Simon M (BMC, 2007)
Abstract Background Bangladesh is committed to the fifth Millennium Development Goal (MDG-5) target of reducing its maternal mortality ratio by three-quarters between 1990 and 2015. Since the early 1990s, Bangladesh has followed a strategy of improving access to facilities equipped and staffed to provide emergency obstetric care (EmOC). Methods We used data from four Demographic and Health Surveys conducted between 1993 and 2004 to examine trends in the proportions of live births preceded by antenatal consultation, attended by a health professional, and delivered by caesarean section, according to key socio-demographic characteristics. Results Utilization of antenatal care increased substantially, from 24% in 1991 to 60% in 2004. Despite a relatively greater increase in rural than urban areas, utilization remained much lower among the poorest rural women without formal education (18%) compared with the richest urban women with secondary or higher education (99%). Professional attendance at delivery increased by 50% (from 9% to 14%, more rapidly in rural than urban areas), and caesarean sections trebled (from 2% to 6%), but these indicators remained low even by developing country standards. Within these trends there were huge inequalities; 86% of live births among the richest urban women with secondary or higher education were attended by a health professional, and 35% were delivered by caesarean section, compared with 2% and 0.1% respectively of live births among the poorest rural women without formal education. The trend in professional attendance was entirely confounded by socioeconomic and demographic changes, but education of the woman and her husband remained important determinants of utilization of obstetric services. Conclusion Despite commendable progress in improving uptake of antenatal care, and in equipping health facilities to provide emergency obstetric care, the very low utilization of these facilities, especially by poor women, is a major impediment to meeting MDG-5 in Bangladesh.